Partial county development plans as a means for preserving wild reindeer habitats in Norway - Hans Olav Bråtå (Rangifer, 2008)
Norwegian wild reindeer habitats are threatened by human intervention. Wild reindeer habitats are joint region wide common pool resources (CPR). Municipalities may be free-riders to that resource if they prefer investments boosting municipal economy despite negative consequences for wild reindeer as a regional resource. Partial county development plans, following the rules of the Planning and Building Act (PBA), are a means that may combine preservation of habitats and development. In order to analyze such plans, theory on CPR management is applied to spatial development planning in the Rondane and Hardangervidda wild reindeer areas. It is shown that the nested system is in accordance with most of Ostrom’s principles. Still, a joint Planning Board ought to be established at Hardangervidda and a partial county plan for the whole wild reindeer area there ought to be established. It is recommended that regular monitoring of interventions and planning is established. Finally, a system or mechanism for low cost conflict resolution is needed; but is not easily included into a system based on official actors at different levels, the planning and building act and public anticipation on equal management. The last point is important for mutual acceptance of restrictions on own activity. Abstract in Norwegian / Sammendrag: Kunnskap om forvaltning av fellesressurer øker forståelsen av regionale planer for villreinområder Norske villreinområder er truet av menneskelige inngrep. Villreinområdene er en regional fellesressurs, men kommunene kan bli gratispassasjerer i forhold til utnytting av denne ressursen ettersom de kan bli fristet til å vektlegge utbygging som gir lokaløkonomiske effekter, på tross av negative konsekvenser for villreinen som en regional ressurs. Fylkesdelplaner, som er basert på plan- og bygningsloven, er et virkemiddel som kan kombinere bevaring og utvikling. For å forstå slike planers muligheter og begrensninger analyses her fylkesdelplanene for Rondane og Hardangervidda øst i forhold til teorier om ...